Gerenciamento integrado de rede local com software livre - Silva, Ápio Carnielo e [UNESP] (2014)
We have developed a graphical interface called Silent Security Monitor (SSM) for use by the web using the PHP languages and shell script, with the aim of decentralizing the management of the network into subdomains, delegating responsibilities to pre-authorized users and have a minimum of technical knowledge on the subject. The SSM interface was made with the integration of different computational resources in the public domain for easy configuration and monitoring necessary services on a network server, such as firewall, DHCP, squid/proxy, DNS, email, among others. In developing the tool we used a modular strategy that facilitates the use and allows the addition of new modules later. Each module developed displays icons that triggered, running in the background triggers in the form of scripts. These in turn performing appropriate for the specific purposes of each service associated with the icon commands. All services available in the tool have a self explanatory text detailing the method of use. The tool was developed entirely with open source software and allows access to your code changes according to user needs